1976
DOI: 10.1128/jvi.18.2.604-618.1976
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free translation of influenza virus mRNA

Abstract: Cytoplasmic poly(A)-rich RNA extracted from fowl plague virus-infected cells was found to program efficiently the translation of two major peptides in the wheat germ cell-free system. These peptides have the same electrophoretic mobility, on polyacrylamide gels, as the two major virion proteins M and NP. I35S]methionine tryptic peptide analysis by one-dimensional paper ionophoresis and finger printing by two-dimensional thin-layer ionophoresis and chromatography show a high degree of similarity between the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…ox Poly(A) of in vitro synthesized RNA. Influt enza viral cRNA synthesized in the infected cell C contains poly(A) (10,13,17). To determine whether the RNA synthesized in vitro also cont tains poly(A), the RNA products were tested for their ability to bind to oligo(dT)-cellulose (Tag ble 3).…”
Section: Resultsmentioning
confidence: 99%
“…ox Poly(A) of in vitro synthesized RNA. Influt enza viral cRNA synthesized in the infected cell C contains poly(A) (10,13,17). To determine whether the RNA synthesized in vitro also cont tains poly(A), the RNA products were tested for their ability to bind to oligo(dT)-cellulose (Tag ble 3).…”
Section: Resultsmentioning
confidence: 99%
“…No in vitro polypeptides were seen to have electrophoretic mobilities near that of the viral glycoprotein. Other investigators have reported an inability to detect synthesis of glycosylated proteins in the wheat germ system (2,4,13). Furthermore, 78K protein was not detected in immunoprecipitates of viral polypeptides synthesized in a reticulocyte cell-free translation system (15).…”
mentioning
confidence: 89%
“…We routinely used 6 x 108 cpm of [35S]methionine per ml. Nevertheless, to keep the specific radioactivity of the methionine as high as possible, we diluted it to 160,000 cpm/pmol, with a final concentration of L-methionine at 4 ,uM.…”
Section: Methodsmentioning
confidence: 99%
“…Influenza viruses are enveloped animal viruses whose genome is composed of a segmented single-stranded RNA, probably entirely "negative stranded" (15,19). This finding is based on several lines of evidence, as follows: (i) the virion RNA is not a template for viral protein synthesis in the wheat germ cell-free system (20), whereas in similar conditions the cytoplasmic polyadenylic acid [poly(A)]-rich RNA from influenza virus-infected cells promotes the synthesis of the major virus structural proteins (4,6,16); (ii) poly(A)-containing mRNA isolated from infected-cell polysomes is entirely complementary to the virion RNA (5,14); and (iii) the virion contains an RNA-dependent RNA polymerase (19).…”
mentioning
confidence: 99%